2010
DOI: 10.1108/13590791011033935
|View full text |Cite
|
Sign up to set email alerts
|

Combating white‐collar crime in Canada: serving victim needs and market integrity

Abstract: Purpose -This paper has two integrated purposes: it provides a report on a symposium hosted by the Bank of Canada and the Royal Canadian Mounted Police in December 2008 dealing with key challenges and directions forward for addressing white-collar crime; and it ties this material into a conceptual review of the academic literature addressing the key conceptual, structural, legal, and cultural issues that impede the effective policing -broadly conceived -of white-collar crime. Design/methodology/approach -Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Numerous research studies have found that feelings of shame, embarrassment, and self-blame contribute to a victim's decision not to report (Button, Lewis, & Tapley, 2014;Shover, Coffey, & Hobbs, 2003). Victims of white-collar crime often experience the same physical and emotional damage seen in street-level offenses: anxiety, depression, distress, anger, helplessness, insecurity, betrayal, self-blame, suicidal ideation, and illness (Copes et al, 2010;Ganzini et al, 1990;Goldney, 1998;Kempa, 2010). According to Croall (2009), white-collar crime against consumers may result in death from unsafe products.…”
Section: Victimization Costs Consequences and Harmmentioning
confidence: 99%
“…Numerous research studies have found that feelings of shame, embarrassment, and self-blame contribute to a victim's decision not to report (Button, Lewis, & Tapley, 2014;Shover, Coffey, & Hobbs, 2003). Victims of white-collar crime often experience the same physical and emotional damage seen in street-level offenses: anxiety, depression, distress, anger, helplessness, insecurity, betrayal, self-blame, suicidal ideation, and illness (Copes et al, 2010;Ganzini et al, 1990;Goldney, 1998;Kempa, 2010). According to Croall (2009), white-collar crime against consumers may result in death from unsafe products.…”
Section: Victimization Costs Consequences and Harmmentioning
confidence: 99%
“…The criminal is a person of respectability, who commits crime in a professional setting, where criminal activities are concealed and disguised in organisational work (Benson & Simpson, ; Bookman, ) by law‐abiding behaviour (Abadinsky, ). The criminal has power and influence (Kempa, ; Podgor, ), and enjoys trust from others in privileged networks (Pickett & Pickett, ).…”
Section: White‐collar Criminalsmentioning
confidence: 99%
“…The types of crime may differ from those of the lower classes, such as business executives bribing public officials to achieve contracts, chief accountants manipulating balance sheets to avoid taxes, and procurement managers approving fake invoices for personal gain. The discussion is summarised by scholars such as Benson and Simpson (2009) ;Blickle et al (2006); Bookman (2008); Brightman (2009) ;Bucy et al (2008); Eicher (2009);Garoupa (2007); Hansen (2009);Heath (2008); Kempa (2010); McKay, Stevens, and Fratzi (2010); Pickett and Picket (2002); Podgor (2007); Robson (2010); and Schnatterly (2003).…”
Section: White-collar Crimementioning
confidence: 99%
“…(); Bookman (); Brightman (); Bucy et al . (); Eicher (); Garoupa (); Hansen (); Heath (); Kempa (); McKay, Stevens, and Fratzi (); Pickett and Picket (); Podgor (); Robson (); and Schnatterly ().…”
Section: Introductionmentioning
confidence: 99%